The Group of Twenty: Input and output legitimacy, reforms, and agenda - Andrew F. Cooper (Asian Development Bank Institute (ADBI), 2012)
The Group of Twenty (G-20) deserves credit for opening up of the "top table" of global governance to a wider representation of countries on a geographic basis in general and Asia in particular. As both a crisis committee in terms of the reverberations from the 2008 financial crisis and a potential global steering committee for a wider set of economic/developmental issues the summit process includes not only the association of leading association of leading emerging economies referred to as BRICS (Brazil, Russia, India, the Republic of China, and South Africa), but key middle powers such as the Republic of Korea. Yet, as a growing body of literature attests, it is clearly the contested nature of the G-20 that has come to the fore. This paper examines both the strengths and weaknesses of the G-20 from the perspective of input and output legitimacy. Notwithstanding some initial successes the constraints with respect to "output" d; have become more acute. Moreover, the "input" legitimacy of the G-20 has been eroded by the absence of the United Nations in the design and representational gaps. On the basis of this analysis the paper examines the debates and makes specific policy recommendations by which regionalism, the engagement of small states (through the role of Singapore and the 3-G coalition), and the expansion of the agenda can be utilized as a dynamic of reform for the G-20 without eroding the core strengths in terms of informality and issue-specific focus of the forum.
Keywords: D7; F02; G01; F55; 330; group of twenty; united nations; regionalism; small states; Internationale Wirtschaftsorganisation; Reform; Politische Entscheidung; Legitimität; Wirtschaftspolitisches Ziel; Weltwirtschaftsordnung; G20-Staaten